KEEFEKTIFAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA PADA PEMBELAJARAN TEMATIK INTEGRATIF KELAS IV SD N 01 PURWOHARJO - Iin Purnamasari, Surya Asri Mahendra Surya Asri Mahendra (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2014)
?óÔé¼?ôThe effectiveness of cooperative learning model type Student Teams Achievement Division toward students?óÔé¼Ôäó motivation and study result on learning thematic integrative in IV class of SD N 01 Purwoharjo?óÔé¼?Ø.The students?óÔé¼Ôäó low motivation on learning thematic integrative caused by the use of unvaried learning and not uses kind of learning model that made the students felt bored. That problem make the students?óÔé¼Ôäó motivation became low and their score still under the KKM. From that problem, need efforts to improve the students?óÔé¼Ôäó motivation and students?óÔé¼Ôäó score. Therefore, the researcher used cooperative learning model type Student Teams Achievement Division. The statements of the problem in this research is ?óÔé¼?ôhow is the?é?á effectiveness of cooperative learning model type Student Teams Achievement Division toward students?óÔé¼Ôäó motivation and study result on learning thematic integrative in IV class of SD N 01 Purwoharjo?. The hypothesis in this research is ?óÔé¼?ôthere is the effectiveness of cooperative learning model, type Student Teams Achievement Division toward students?óÔé¼Ôäó motivation and study result on learning thematic integrative in IV class of SD N 01 Purwoharjo. The objective of the research is to know the effectiveness of cooperative learning model type Student Teams Achievement Division toward students?óÔé¼Ôäó motivation and study result on learning thematic integrative in IV class of SD N 01 Purwoharjo. Type of this research is Quantitative. The experimental method was the method that used in this research. The population in this research is four grade students of SD Negeri 01 Purwoharjo. The sample was taken as many as 52 students, consists of 26 students of four A class and 26 students of four B class. Methods of data collection in this research are the test, documentation, and observation. The research design was the posttest only control group design.Based on the result analysis of the data after getting the treatment, average score in experimental class before getting treatment was 76,5 increased to 82,4. The students learning achievement in experimental class was 88% and in control class was 69%.From the result of T-test, the researcher get ttest = 2.16 and ttable = 2.00. Therefore, ttest> ttable, and H1 was accepted. Afterwards, from the calculation of learning motivation classical achievement test, experimental class 84 % and control class 78%. The conclusion is cooperative learning model type Student Teams Achievement Division effective to increase students?óÔé¼Ôäó motivation and study result on learning thematic integrative in four grade students of SD N 01 Purwoharjo.Suggestion that can be drawn from this research is a cooperative learning model should be the type of Student Teams Achievement Division can become reference in a learning strategy.